2004
DOI: 10.1242/dev.01266
|View full text |Cite
|
Sign up to set email alerts
|

Disrupted gonadogenesis and male-to-female sex reversal inPod1knockout mice

Abstract: approaches demonstrated that Pod1 transcriptionally represses steroidogenic factor 1 (Sf1/Nr5a1/Ad4BP), an orphan nuclear receptor that regulates the expression of multiple genes (including Scc) that mediate sexual differentiation. Our results establish that Pod1 is essential for gonadal development, and place it in a transcriptional network that orchestrates cell fate decisions in gonadal progenitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
148
1
9

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 162 publications
(166 citation statements)
references
References 45 publications
6
148
1
9
Order By: Relevance
“…At later stages Pod1 expression becomes sexually dimorphic and it is found in the testis interstitium but not within the ovary [65]. Pod1 was shown to repress Sf-1 expression in tissue culture experiments [65][66][67]. Consistent with this, Pod1 deficient embryos showed an expanded Sf-1 expression domain at the boundary between the gonad and mesonephros.…”
Section: Page 7 Of 23mentioning
confidence: 63%
See 1 more Smart Citation
“…At later stages Pod1 expression becomes sexually dimorphic and it is found in the testis interstitium but not within the ovary [65]. Pod1 was shown to repress Sf-1 expression in tissue culture experiments [65][66][67]. Consistent with this, Pod1 deficient embryos showed an expanded Sf-1 expression domain at the boundary between the gonad and mesonephros.…”
Section: Page 7 Of 23mentioning
confidence: 63%
“…Although Pod1 was not directly involved in adrenal development, its disruption prevented the physical separation between the gonad and adrenal primordia. Interestingly, there was no increase in adrenal markers expression in the gonad which suggested that differentiation and sorting of the precursors were not affected [66]. Thus Pod1 acts to restrict Sf-1 expression such that the adrenal and gonad primordia are separated during development.…”
Section: Page 7 Of 23mentioning
confidence: 96%
“…In Sf1 heterozygous embryos, Dhh expression was temporarily reduced at E11.5, and fetal Leydig cell markers Cyp17 and Cyp11a1 were reduced at E13.5 [58], suggesting an indirect role for SF1 in initial fetal Leydig differentiation via DHH. Additionally, a null mutation of Pod1, a helix-turn-helix transcription factor expressed in the gonadal interstitium, increased the number of steroidogenic cells in both male and female gonads but reduced androgen production [59]. These results indicate that fetal Leydig cell differentiation is controlled externally through pathways elicited by Sertoli cells and intrinsically by transcription factors.…”
Section: From Sry To Androgensmentioning
confidence: 86%
“…and fixed in 4% PFA. Ten-micrometer cryosections were prepared as described previously (16). The primary antibodies used were anti-␣ 8 integrin (1:1500 dilution).…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…The immunofluorescent staining procedure was described previously (16). The secondary antibodies used were FITC-conjugated goat anti-rabbit IgG (Jackson Laboratories, West Grove, PA; 1:400) to detect anti-␣ 8 integrin and Cy3-conjugated donkey anti-mouse IgG (Jackson Laboratories, 1:500) to detect anti-lacZ.…”
Section: Immunohistochemistrymentioning
confidence: 99%